The cost and cost‐effectiveness of childhood cancer treatment in El Salvador, Central America: A report from the Childhood Cancer 2030 Network. Issue 2 (15th September 2017) - Fuentes‐Alabi, Soad; Bhakta, Nickhill; Vasquez, Roberto Franklin; Gupta, Sumit; Horton, Susan E.
Abstract : BACKGROUND: Although previous studies have examined the cost of treating individual childhood cancers in low‐income and middle‐income countries, to the authors' knowledge none has examined the overall cost and cost‐effectiveness of operating a childhood cancer treatment center. Herein, the authors examined the cost and sources of financing of a pediatric cancer unit in Hospital Nacional de Ninos Benjamin Bloom in El Salvador, and make estimates of cost‐effectiveness. METHODS: Administrative data regarding costs and volumes of inputs were obtained for 2016 for the pediatric cancer unit. Similar cost and volume data were obtained for shared medical services provided centrally (eg, blood bank). Costs of central nonmedical support services (eg, utilities) were obtained from hospital data and attributed by inpatient share. Administrative data also were used for sources of financing. Cost‐effectiveness was estimated based on the number of new patients diagnosed annually and survival rates. RESULTS: The pediatric cancer unit cost $5.2 million to operate in 2016 (treating 90 outpatients per day and experiencing 1385 inpatient stays per year). Approximately three‐quarters of the cost (74.7%) was attributed to 4 items: personnel (21.6%), pathological diagnosis (11.5%), pharmacy (chemotherapy, supportive care medications, and nutrition; 31.8%), and blood products (9.8%). Funding sources included government (52.5%), charitable foundations (44.2%), and a social security contribution scheme (3.4%). Based on 181 new patients per year and a 5‐year survival rate of 48.5%, the cost per disability‐adjusted life‐year averted was $1624, which is under the threshold considered to be very cost effective. CONCLUSIONS: Treating childhood cancer in a specialized unit in low‐income and middle‐income countries can be done cost‐effectively. Strong support from charitable foundations aids with affordability. Cancer 2018;124:391‐7 . © 2017 American Cancer Society . Abstract : The results of the current study indicate that the treatment of patients with selected pediatric cancers in a specialized unit in El Salvador can achieve good outcomes at a cost per newly diagnosed case of US $28, 707 and a cost per life saved of $58, 586. This meets the World Health Organization threshold of being "very cost effective." Strong support from local foundations is important in making treatment affordable.